Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas

Active and durable alkaline earth metal substituted perovskite catalysts for dry reforming of methane - Dama, Srikanth; Ghodke, Seema R.; Bobade, Richa; Gurav, Hanmant R.; Chilukuri, Satyanarayana (Applied Catalysis B - Environmental, 2018)
Dry reforming of methane is an important process for the utilization of CO2 and to get valuable synthesis gas. Alkaline earth metal substituted MZr1-xNixO3-delta perovskites were synthesized by citrate gel method, characterized and evaluated for dry reforming methane. Characterization results show that the type of alkaline earth substituted at the A site of the perovskite oxide plays an important role in terms of structure, basicity, oxygen deficiency and Ni dispersion. Calcium substituted CaZr0.8Ni0.2O3-delta catalyst shows superior activity in terms of high CH4 and CO2 conversion, while maintaining the activity even after 500 h of reaction. Mechanistic investigations were carried out using transient pulse experiments and insitu FTIR-diffuse reflectance spectroscopy. These experiments reveal that redox property and basicity play important role in activation and sustaining the reforming reaction. Insitu FTIR measurements show that surface hydroxyl groups of the support are vital for high activity and durability of CaZr0.8Ni0.2O3-delta catalyst. XRD and TGA analysis of catalysts after reaction show the structures are retained, but peaks pertaining to coke were observed on SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts. On the otherhand, CaZr0.8Ni0.2O3-delta catalyst had only amorphous carbon even after 500 h of reaction. HRTEM studies revealed that SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts deactivated mostly due to the formation of carbon nanotubes with Ni embedded in them. Raman and XPS analysis helped in identifying types of coke precursors present on the catalysts. The investigation also illustrate that type of carbon formed depends on the basicity of perovskite oxide, metal to support interaction, Ni crystallite size, surface hydroxyl groups and oxygen defects. This study clearly demonstrated that CaZr0.8Ni0.2O3-delta is an excellent catalyst for dry reforming reaction with long life.

Tuning the dimensionality of layered Srn+1Tin−xNixO3n+1 perovskite structures for improved activity in syngas generation - Dama, Srikanth (Journal of Catalysis, 2018)
Interest in perovskite type oxides is growing due to their versatile catalytic applications. A series of Ruddlesden-Popper (RP) type layered perovskite oxides Srn+1Tin−xNixO3n+1 were prepared and evaluated for their catalytic activity in steam reforming, CO2 reforming and bi-reforming of methane. These materials, prepared through citrate gel method were characterized to understand their structure and Ni reducibility. Substitution of Ni in RP phases was established through refinement of XRD powder pattern. During methane reforming, the catalytic activity increased with the order of RP phase of SrTi1−xNixO3−δ (n = ∞). TPR results show variation in Ni reducibility with the order of RP phase, while TPD-O2 study helped to estimate oxygen vacancies. These vacancies seem to influence catalytic activity during methane reforming. Transient pulse experiments show that CO2 dissociates over oxygen vacancies to give CO and oxygen, with later replenishing lattice oxygen in SrTi0.8Ni0.2O3−δ (n = ∞) phases. Highly labile oxygen vacancies generated in the bulk of SrTi0.8Ni0.2O3−δ must be migrating to the surface, helping in the removal of coke formed. Characterization of catalysts after reaction helped in better understanding of coke precursors.
Keywords: Dry reforming; NickelSyngas; Ruddlesden-Popper (RP) perovskites; Steam reforming